YouTube's Most Viewed Videos - Haniff, Baharudin; Kam, Raslan; Mohd Azmyl, Md Yusof *; Zan, Azlee (BFM Media Sdn Bhd, 2023)
Azmyl Yunor and Zan Azlee join Kam Raslan in this episode of A Bit of Culture to dissect and analyse recent events. Azmyl starts off by sharing his frustrations of yet another music venue being raided by the authorities and then wonders whether we should be allowed to vote for our own mayor. Kam then shares his experience going through Youtube’s most viewed videos and how he does not recognise most of them. He then asks whether he should still try to be in touch with recent trends, or ignore them completely. In the second part of the show, Zan gives his thoughts on the new film classifications that were recently released.